SPEECH AND STRATEGY: UNPACKING POLITICAL POWER IN INDIA THROUGH THE LANGUAGE OF POWER - Patteti, Prof. Raja Sekhar; D., Rajani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Language plays a pivotal role in shaping political power dynamics within India's complex and diverse linguistic landscape. In a country with a multitude of languages and dialects, political parties—both national and regional—use language as a tool to influence, mobilize, and maintain control over various constituencies. This analysis delves into the rhetorical techniques employed by these parties, focusing on strategies such as circumlocution, deliberate ambiguity, language shifting, and the ongoing debates surrounding language policy. These tools are carefully deployed to frame policies, assert and reinforce regional identities, signal social reform orientations, justify controversial actions, and extend political appeal across a broad spectrum of voters. By examining case studies, the paper demonstrates how language is integral to political messaging, enabling parties to position themselves strategically within the competitive electoral landscape. Additionally, it highlights the role of language in shaping political discourse, influencing public perception, and maintaining power structures at both the regional and national levels. This study provides valuable insights into the deeper regional tensions, social reform movements, and the intricate power relations that underpin India's political system, underscoring the significant impact of language in shaping the nation’s political future.